Long-Term Peritoneal Dialysis Experience: Quality Control Supports the use of Fluconazole to Prevent Fungal Peritonitis. Issue 7 (July 2013) - Lopes, Karina; Rocha, Ana; Rodrigues, Anabela; Carvalho, Maria João; Cabrita, António
Background: Fungal peritonitis (FP) is rare, but it is associated with high morbidity and mortality. Patients and Methods: A prospective study was conducted based on the peritonitis episodes registry to evaluate FP rate, possible risk factors, and outcomes. The impact of prophylactic intervention with oral fluconazole was evaluated. Results: Over 24 years of experience, 417 patients underwent peritoneal dialysis (PD), followed for 956 patient-years. By the end of the study, the peritonitis rate reached 0.47 episodes per patient-year of treatment (ep/pt-y). FP was detected in 24 patients. The global rate of FP was 0.03 ep/pt-y (4.8%). Candida species accounted for 92% of the FP. Risk factors identified: recent use of antibiotics in 63% (13 episodes of bacterial peritonitis and 2 exit-site infections (ESI)) and immunosuppressive therapy in 8%. While rare, the FP proportion was still observed to increase from the beginning of the program, reaching 7.8% (0.05 ep/pt-y). A strategy of antifungal prophylaxis with oral fluconazole during peritonitis or ESI antibiotic therapy was adopted, which allowed thereafter a 4.0% falling FP proportion (by study end, rate of 0.01 ep/pt-y). Catheter removal occurred in all patients. The mortality rate was 12.5%. Reinsertion of dialysis catheter was attempted in 4 patients and PD was successfully resumed in 3 patients. Conclusions: FP was associated with high mortality and required early removal of the catheter in all patients. Recent use of antibiotics was a predisposing factor to PF The quality control process determined a prophylactic strategy and reduction of PF after introduction of oral fluconazole was implemented.